Pengaruh Politik Hukum Amerika Serikat Terhadap Konflik Global Dan Dampaknya Pada Politik Hukum Indonesia - Prabowo, Andrianto; Irma Mangar; Nico Ferdian (Diktum: Jurnal Ilmu Hukum, 2026)
This research aims to analyze the influence of the political law of the United States on the dynamics of global conflicts and its impact on the development of legal politics in Indonesia. The method used is a qualitative approach with descriptive analysis of various international legal and political phenomena. The results of the study show that the legal politics of the United States have an expansive and strategic character, where the law is used as an instrument to legitimize global geopolitical interests. Policies such as the "War on Terror", military intervention, and the application of economic sanctions play a role in shaping and influencing global conflicts. Furthermore, the global conflict has a significant impact on Indonesian legal politics, both in the fields of security, economy, and human rights. Indonesia has shown a tendency to adapt its legal policies to global dynamics, including in the formation of anti-terrorism regulations, trade policy adjustments, and the adoption of international legal standards. However, the process also poses a dilemma between global demands and efforts to defend national legal sovereignty. The conclusion of this study shows that the relationship between the legal politics of the United States, global conflicts, and Indonesian legal politics is complex and interdependent. Therefore, an adaptive, selective, and national interest-oriented legal political strategy is needed in order to be able to face global dynamics without sacrificing the rule of law.